Education on Managing Hypertension with Self-Acupressure and Cucumber Lemon Juice for the Elderly at Nusa Indah Senja Posbindu, Depok: Community Services Faculty of Health Sciences, Universitas Nasional, Indonesia - Novi, Novita Sari (Rajaki of Tulip Medika Publisher, 2025)
Hypertension is a condition in which a person experiences an increase in blood pressure above the normal threshold that can cause pain and even death. A person is said to have hypertension if their blood pressure exceeds the normal limit, which is more than 140/90 mmHg. The risk factors for hypertension include age, genetics, and lifestyle. If hypertension is not well controlled and occurs continuously, it can lead to various complications such as stroke, kidney disease, heart disease, and even death. Based on data collected at Nusa Indah Posbindu at dusk RT 02 Gandul Village, Cinere District, Depok, West Java, data from January to April 2025 showed that 33.3%-42.1% of the elderly have a history of hypertension. The purpose of this counseling activity for the elderly in the posbindu area is to educate the community on how to manage and control hypertension using self-acupressure techniques and the administration of cucumber lemon juice. The methods used include the presentation of material through PowerPoint, question and answer discussions, distribution of leaflets, educational fans, acupressure aids, direct practice of self-acupressure steps for hypertension, and the administration of cucumber lemon juice. The results of this activity showed that all participants received the information well, were able to understand the presentation about hypertension and the therapy provided, and could directly practice self-acupressure therapy to manage hypertension. Additionally, participants directly tried the cucumber lemon juice and all liked it. Keywords: Self-Acupressure, Cucumber Lemon Juice, Hypertension